2013
DOI: 10.11118/actaun201361051431
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mineral fertilization on belowground plant biomass of grassland ecosystems

Abstract: TOMAŠKIN JÁN, JANČOVIČ JÁN, VOZÁR ĽUBOŠ, TOMAŠKINOVÁ JUDITA: The eff ect of mineral fertilization on belowground plant biomass of grassland ecosystems. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2013, LXI, No. 5, pp. 1431-1440 Aim of the work was to determine the eff ect of diff erent doses of mineral fertilization on belowground and aboveground plant biomass production of three diff erent types of grasslands, to state R:S ratio (root:shoot) and turnover period of belowground plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…Heggenstaller et al (2009) emphasized that nitrogen fertilization has a positive effect on yieldand root biomass of grasses. In addition, some studies have reported that fertilization increases root biomass (Tewari and Joshi, 1985;Rajaniemi et al, 2003;Tomaškin et al, 2013); nevertheless, low dose fertilization increases root biomass and high doses cause a decrease (Holub et al, 2013). The data of the current study differed from other researchers (Pucheta et al, 2004;Glab and Kacorzyk, 2011;Ladwig et al, 2012;Balogianni et al, 2014), due to different environmental conditions and management applications (Nippert et al, 2012;Yan et al, 2013), different amounts of fertilizer (Holub et al, 2013) and different grazing intensity and ungrazing applications (McNaughton et al, 1998).…”
Section: Root Biomasscontrasting
confidence: 77%
“…Heggenstaller et al (2009) emphasized that nitrogen fertilization has a positive effect on yieldand root biomass of grasses. In addition, some studies have reported that fertilization increases root biomass (Tewari and Joshi, 1985;Rajaniemi et al, 2003;Tomaškin et al, 2013); nevertheless, low dose fertilization increases root biomass and high doses cause a decrease (Holub et al, 2013). The data of the current study differed from other researchers (Pucheta et al, 2004;Glab and Kacorzyk, 2011;Ladwig et al, 2012;Balogianni et al, 2014), due to different environmental conditions and management applications (Nippert et al, 2012;Yan et al, 2013), different amounts of fertilizer (Holub et al, 2013) and different grazing intensity and ungrazing applications (McNaughton et al, 1998).…”
Section: Root Biomasscontrasting
confidence: 77%
“…In our experiment in pots, we established that the increasing amounts of applied N had an effect on the distribution of formed biomass of the root system. The specific N-stimulating influence on root biomass production in grasslands (Tomaškin et al, 2013) is apparently not expressed in miscanthus. We have found, with the increase in the quantities of applied N, that the percentage of the mass of roots and small roots after harvest, in the second season of miscanthus growing, increases, to the detriment of the rhizome mass (Table 1).…”
Section: Discussion Distribution Of the Root System Biomassmentioning
confidence: 96%
“…In general, the BGB was greater by a factor of 3.15. In many grasslands, BGB plant biomass is greater than AGB biomass, in some cases even by a factor of five or more (Tomaškin et al 2013) and this is even typically greater in grasslands with high water and nutrient limitations like in our monitored grasslands (Blair et al 2014). The total DMY (Table 3) shows no significant differences between the five sites.…”
Section: Discussionmentioning
confidence: 60%